42nd Winter School on Wave and Quantum Acoustics 41th Winter School on Vibroacoustical Hazards Suppressions - URBAŃCZYK, Marian (Archives of Acoustics, 2013)
Szczyrk, Poland, February 25 – March 1, 2013